Quantum states of hydrogen cations confined into spherical and nanotube-like potential wells: H2+, H3+ (C2h and C2v) and H3+ (D3h). (4th October 2021) - Micca Longo, Gaia; Francesco Cantatore, Aldo; Stripoli, Carla; Giordano, Domenico; Longo, Savino
Abstract: In this work, the potential energy surfaces (PESs) of hydrogen-based cations H 2 + and H 3 + placed inside infinite potential wells, in the shape of an infinite cylinder and a sphere, are investigated. The calculations are performed using the diffusion Monte Carlo (DMC) technique. Different symmetries are studied, some of them for the first time. The PESs trends are rationalized. The Raman shift of A 1 ′ mode of spherically confined H 3 + is also calculated.